Risky dis/entanglements: Torture and sexual violence in conflict. (December 2019) - Gray, Harriet; Stern, Maria
Conflict-related sexual violence has become increasingly recognized in international spaces as a serious, political form of violence. As part of this process, distinctions between the categories of 'sexual violence' and 'torture' have blurred as scholars and other actors have sought to capitalize on the globally recognized status of torture in raising the profile of sexual violence. This move, while perhaps strategically promising, even already fruitful, prompts us to heed caution. What might we inadvertently engender by further pursuing such positioning? While torture and sexual violence have both been widely framed within the academic literature as strategic in recent decades, only torture, and not sexual violence, has emerged from elements of this literature as (potentially) legitimate, despite the slippages between them as categories of violence. This article offers one avenue for thinking through what an invigorated focus on sexual torture as a category of violence might unwittingly render possible, and thus for reflecting on the possible stakes of collapsing the categories of sexual violence and torture. Ultimately, we argue that we should perhaps resist the urge to frame sexual violence as torture and instead cleave to the sticky signifier of 'the sexual', despite the ways in which it has served to normalize, perpetuate and obfuscate grievous harms throughout history.